The Influence of The Principal’s Leadership Style n Employee Performance and Well-Being at Institutional Education - Erly Juliyani; M. Chotibuddin; Ahmad Iwan Zunaih; Nashihin (Islamic Education Management Study Program, Faculty of Tarbiyah, Sunan Drajat Islamic Boarding School Institute, Lamongan, East Java, Indonesia., 2025)
This study aims to analyze the influence of the principal's leadership style on employee performance and well-being at SMK Sunan Drajat Lamongan. Leadership style is a crucial factor in school management that contributes to employee motivation, productivity, and job satisfaction. A quantitative research approach was employed, utilizing simple and multiple linear regression analysis techniques. The study sample consisted of 50 respondents, comprising school staff and employees.The results indicate that the principal's leadership style significantly affects employee performance, with a regression coefficient of 0.65 and a p-value of 0.000. The influence on employee well-being is also significant, with a regression coefficient of 0.58 and a p-value of 0.002. Simultaneously, the leadership style accounts for 72% of the variation in employee performance and well-being (R² = 0.720). These findings confirm that the implementation of an appropriate leadership style, particularly transformational leadership, can foster a productive work environment and support employeewell-being.